"It's for their own good": Techniques of neutralization and security guard violence against psychiatric patients. (April 2016) - Johnston, Matthew S; Kilty, Jennifer M
Based on eight in-depth interviews conducted with security guards who work in the psychiatric units of two hospitals located in Ottawa, Canada, this research found that private security agents unknowingly draw on Sykes and Matza's five techniques of neutralization to justify their use of violence and coercive force against patients and to overcome their feelings of guilt for participating in the administration of brutal intervention practices, including physical and chemical restraints. Guards claimed that these practices benefit the patients more than it hurts them and in cases where they believed the interventions to be unwarranted, guards either accepted the medical staff's judgment to make decisions about when coercive force should be used or condemned the authority the nursing staff has in determining how to manage patients. They also drew on militant codes of security conduct to justify their tough demeanours and resilient attitudes towards medicalized violence. Implications for forensic practice include considerations of the effects of the (gendered) power relations that structure closed institutional settings and can harm already vulnerable patients, as well as the negative consequences of using security to enforce arbitrary institutional rules.